2016
DOI: 10.1038/srep28767
|View full text |Cite|
|
Sign up to set email alerts
|

One Step Quantum Key Distribution Based on EPR Entanglement

Abstract: A novel quantum key distribution protocol is presented, based on entanglement and dense coding and allowing asymptotically secure key distribution. Considering the storage time limit of quantum bits, a grouping quantum key distribution protocol is proposed, which overcomes the vulnerability of first protocol and improves the maneuverability. Moreover, a security analysis is given and a simple type of eavesdropper’s attack would introduce at least an error rate of 46.875%. Compared with the “Ping-pong” protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In this paper, a new quantum key distribution protocol HQKD is proposed and the security of this protocol is analyzed for intercept-measure-resend (IR) attack and entanglementmeasure attack. HQKD protocol doesn't need to store the quantum states and improves the maneuverability, the position of hyperentangled Bell state is used to encode information and detect eavesdroppers.Compared with [44], 6 bits classical information can be encoded by a hyperentangled Bell state and single particle, this protocol is with higher information transmission efficiency.Compared with OPP protocol, the HQKD protocol is with higher eavesdropping detection efficiency 93.75% when Eve wants to get all the information. The protocol needs to fabricate and measure single particle, which can be implemented by using single photon source, single photon detectors and linear optical devices, this protocol also needs to fabricate and measure hyperentangled Bell states, which has been experimentally realized [48], [49], but based on the existing technical conditions, there are some difficulties in realizing to mix hyperentangled Bell states and single particle, quantum experiments have developed rapidly in recent years and the research of mixing hyperentangled Bell states and single particle will be research focus, we believe that the problem will be solved with the advancement of technology.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, a new quantum key distribution protocol HQKD is proposed and the security of this protocol is analyzed for intercept-measure-resend (IR) attack and entanglementmeasure attack. HQKD protocol doesn't need to store the quantum states and improves the maneuverability, the position of hyperentangled Bell state is used to encode information and detect eavesdroppers.Compared with [44], 6 bits classical information can be encoded by a hyperentangled Bell state and single particle, this protocol is with higher information transmission efficiency.Compared with OPP protocol, the HQKD protocol is with higher eavesdropping detection efficiency 93.75% when Eve wants to get all the information. The protocol needs to fabricate and measure single particle, which can be implemented by using single photon source, single photon detectors and linear optical devices, this protocol also needs to fabricate and measure hyperentangled Bell states, which has been experimentally realized [48], [49], but based on the existing technical conditions, there are some difficulties in realizing to mix hyperentangled Bell states and single particle, quantum experiments have developed rapidly in recent years and the research of mixing hyperentangled Bell states and single particle will be research focus, we believe that the problem will be solved with the advancement of technology.…”
Section: Discussionmentioning
confidence: 99%
“…In both the schemes proposed in Ref. 1 and summarized here, the authors claimed that the security arises due to Heisenberg's uncertainty principle and no-cloning. However, it should be noted that the security in a cryptographic protocol is achieved using splitting the useful information in 2 or more pieces, in such a way that unavailability of all these pieces makes it impossible to extract the secret.…”
Section: Analysis Of LI Et Al's Protocolmentioning
confidence: 92%
“…Further, it is also shown that all the error rates computed in the Li et al's paper are incorrect as the authors failed to recognize the fact that any eavesdropping effort will lead to entanglement swapping. Finally, it is established that Li et al's scheme can be viewed as an incrementally (but incorrectly) modified version of the existing schemes based on Goldenberg Vaidman (GV) subroutine.Recently, Li et al 1 have proposed a one step scheme for quantum key distribution (QKD) using a Bell states. The scheme is not secure and the claims made by the authors unfortunately appear to be inaccurate for various reasons as elaborated in this comment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…But there is still a serious problem on how to distribute the key safely. [3][4][5] Different from the classical secure communication protocol, quantum secure communication (QSC) protocol is based on the fundamental laws of quantum physics rather than the complexity of computing. So QSC has much higher performance of security.…”
Section: Introductionmentioning
confidence: 99%